Transvesical natural orifice transluminal endoscopic surgery (NOTES) nephrectomy with kidney morcellation: a proof of concept study - Lima, Estêvão Augusto Rodrigues de (2012)
The authors acknowledge Karl Storz, Richard Wolf and Covidien for their support with equipment.